Self-management in patients with psoriasis - Pathak SN (Dove Medical Press, 2014)
Swetha Narahari Pathak,1 Pauline L Scott,1 Cameron West,1 Steven R Feldman,1–3 1Center for Dermatology Research, Departments of Dermatology, 2Center for Dermatology Research, Departments of Pathology, 3Public Health Sciences, Wake Forest School of Medicine, Winston-Salem, NC, USA Abstract: Psoriasis is a chronic inflammatory disorder effecting the skin and joints. Additionally, multiple comorbidities exist, including cardiovascular, metabolic, and psychiatric. The chronic nature of psoriasis is often frustrating for both patients and physicians alike. Many options for treatment exist, though successful disease management rests largely on patients through the application of topical corticosteroids, Vitamin D analogs, and calcineurin inhibitors, amongst others and the administration of systemic medications such as biologics and methotrexate. Phototherapy is another option that also requires active participation from the patient. Many barriers to effective self-management of psoriasis exist. Successful treatment requires the establishment of a strong doctor-patient relationship and patient empowerment in order to maximize adherence to a treatment regimen and improve outcomes. Improving patient adherence to treatment is necessary in effective self-management. Many tools exist to educate and empower patients, including online sources such as the National Psoriasis Foundation and online support group, Talk Psoriasis, amongst others. Effective self management is critical in decreasing the physical burden of psoriasis and mitigating its multiple physical, psychological, and social comorbidities, which include obesity, cardiovascular disease, alcohol dependence, depression, anxiety, and social anxiety. Keywords: psoriasis, adherence, self management, compliance